The Influence of Agricultural Labor, Domestic Investment, and Government Expenditure on The Growth of The Agricultural Sector in West Java - Lestari, Anisa Septia Wahyu; A., Karla Delfina; M.A, Intan Nurluqyana; Wati, Dewi Rohma (JURNAL EMA (Ekonomi Manajemen Akuntansi), 2025)
This study aims to analyze the effect of agricultural labour, government expenditure, and domestic investment on agricultural sector growth in West Java during the period 2004-2023. The study used secondary time series data processed using multiple linear regression. The results showed that simultaneously the three variables had a significant influence on agricultural sector growth, with a coefficient of determination of 92,7%. However, partially only government spending had a significant influence, while agricultural labour and domestic investment showed no significant influence.